2015
DOI: 10.1080/10408398.2013.814044
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, Health, and Technological Functionality of Lupin Flour Addition to Bread and Other Baked Products: Benefits and Challenges

Abstract: Lupin is an undervalued legume despite its high protein and dietary fiber content and potential health benefits. This review focuses on the nutritional value, health benefits, and technological effects of incorporating lupin flour into wheat-based bread. Results of clinical studies suggest that consuming lupin compared to wheat bread and other baked products reduce chronic disease risk markers; possibly due to increased protein and dietary fiber and bioactive compounds. However, lupin protein allergy has also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 143 publications
(18 reference statements)
1
58
0
Order By: Relevance
“…In addition to high protein content, lupin seeds contain considerable amounts of phytochemical compounds with potential beneficial effects on human health, such as phenolic compounds, phytosterols, tocopherols and squalene . In vitro and in vivo studies have shown that the consumption of lupin‐based food products reduces the risk of dyslipidemia, diabetes, obesity, hypertension and intestinal dysfunction . Beneficial health effects are probably caused by the synergistic action of lupin seed components, including specific proteins, fiber and bioactive compounds …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to high protein content, lupin seeds contain considerable amounts of phytochemical compounds with potential beneficial effects on human health, such as phenolic compounds, phytosterols, tocopherols and squalene . In vitro and in vivo studies have shown that the consumption of lupin‐based food products reduces the risk of dyslipidemia, diabetes, obesity, hypertension and intestinal dysfunction . Beneficial health effects are probably caused by the synergistic action of lupin seed components, including specific proteins, fiber and bioactive compounds …”
Section: Resultsmentioning
confidence: 99%
“…4 In vitro and in vivo studies have shown that the consumption of lupin-based food products reduces the risk of dyslipidemia, diabetes, obesity, hypertension and intestinal dysfunction. 31,32 Beneficial health effects are probably caused by the synergistic action of lupin seed components, including specific proteins, fiber and bioactive compounds. 31 The most numerous phenolic compounds found in lupin seeds belong to phenolic acids, flavones, and isoflavones.…”
Section: Characteristics Of Native Phenolic Compounds Interacting Witmentioning
confidence: 99%
“…In order to meet the global demand for edible oils, it is of utmost importance to identify new oil seeds e/o crops that could contribute towards increasing the supply. Lupin ( Lupinus ) is a legume that is generally consumed in processed forms, and its protein and fiber fractions are found in several food products, for example, beverages, bread, and pasta . In addition, lupin provides relatively high levels of lipids (about 10% w/w), which have been investigated to a limited extent hitherto.…”
Section: Introductionmentioning
confidence: 99%
“…Peanut and soybean are two of the eight foods that account for the most significant food allergies in the US and Europe . Furthermore, other legumes, such as lupine, have been increasingly used in Europe in flour form, as an additive for wheat flour . The potential of lupine allergens to elicit allergic reactions has been documented since the early 1990s, initially reported as a result of cross‐reactivity with peanut allergens but later also described as primary sensitization .…”
Section: Introductionmentioning
confidence: 99%